2000
DOI: 10.1063/1.1289906
|View full text |Cite
|
Sign up to set email alerts
|

Transparent p-type conducting CuScO2+x films

Abstract: Electrical and optical properties of p-type CuFe1-xSnxO2 (x = 0.03, 0.05) delafossite-oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(157 citation statements)
references
References 6 publications
7
149
0
1
Order By: Relevance
“…As the conduction band of CuScO 2 is composed of mainly Sc 3d states which do not interact as strongly due to their more localized nature, the dispersion is lessened. Both the VBM and CBM occur at L, indicating CuScO 2 to be a direct gap semiconductor as shown previously [40,51] with a band gap of 2.84 eV, slightly underestimated from its experimental value of 3.3 eV [16]. As this transition is symmetry-allowed [40], better agreement between calculated and experimental values is seen compared to CuInO 2 and CuGaO 2 .…”
Section: Cuscosupporting
confidence: 57%
See 2 more Smart Citations
“…As the conduction band of CuScO 2 is composed of mainly Sc 3d states which do not interact as strongly due to their more localized nature, the dispersion is lessened. Both the VBM and CBM occur at L, indicating CuScO 2 to be a direct gap semiconductor as shown previously [40,51] with a band gap of 2.84 eV, slightly underestimated from its experimental value of 3.3 eV [16]. As this transition is symmetry-allowed [40], better agreement between calculated and experimental values is seen compared to CuInO 2 and CuGaO 2 .…”
Section: Cuscosupporting
confidence: 57%
“…The effective masses for the VBM and CBM of CuInO 2 and CuGaO 2 were calculated at F and , respectively, while those for CuScO 2 were both calculated at L. The VBM effective masses for ptype conductivity for CuInO 2 and CuGaO 2 were found to be has its VBM at L. We have also calculated the effective masses along the high symmetry directions and found that CuInO 2 possesses a lower effective mass of 0.58m 0 in the F-direction and CuGaO 2 has a lower effective mass of 0.46m 0 also in the F-direction. The VBM effective mass data thus follow the experimental p-type conductivity trend with CuScO 2 having the lowest calculated effective mass and the highest reported conductivity [16,20], while CuInO 2 has the lowest reported conductivity [17] of the compounds and the largest effective mass. As CuInO 2 can be bipolar doped, it is of interest to examine the conduction band effective mass for each compound to determine its electron effective mass for n-type conductivity.…”
Section: Effective Massmentioning
confidence: 91%
See 1 more Smart Citation
“…[61] With a free carrier density of holes of N h = 1.3 × 10 17 cm −3 and a hole mobility at ≈10 cm 2 V −1 s −1 , the conductivity (<1 S cm −1 ) was much lower than of n-type TCOs. Subsequently, other Cu-based delafossites with Al replaced by other metal cations, such as Cr, [62] Fe, [63] Sc, [64] and Y, [65] were investigated with oxygen intercalation and various synthesis methods (and thus, various microstructures) with the aim of decreasing the dopant compensation and increasing mobility (Figure 1). Recently, the CuCrO 2 has been explored with promising results; Mg-doped CuCrO 2 has the highest p-type conductivity reported for an oxide to date, 220 S cm −1 .…”
Section: P-type Transparent Conductorsmentioning
confidence: 99%
“…6 To date, much of the research on p-type TCOs has focused on materials with the delafossite structure such as CuAlO 2 7 or CuScO 2 . 8 Recently, p-type ZnO with hole concentrations near 10 20 1/cm 3 was prepared via a metastable codoping process incorporating N-Ga-N associates. 6,9,10 Previously, the phenomenon of codoping has been known to give rise to extensive n-type TCO solid solutions.…”
Section: Reports Of High Mobilitymentioning
confidence: 99%